MELTING HEAT TRANSFER OF UNSTEADY MHD BOUNDARY LAYER FLOW OF EYRING-POWELL NANOFLUID PAST AN INCLINED STRETCHING SHEET - REDDY.N*, VIJAYA BHASKAR; NAIKOTI, KISHAN (International Journal of Mathematical Archive, 2018)
This paper deals with the viscous incompressible magnetohydrodynamic boundary layer unsteady flow of an Eyring-Powell nanofluid over an inclined melting stretching sheet in the presence of radiation and non-uniform heat source/sink effects has been investigated numerically. The resulting nonlinear governing partial differential equations with associated boundary conditions of the problem has formulated and transformed into a non-similar form. The resultant equations are then solved numerically using Runge-Kutta fourth order method along with shooting technique. The physical significance of different parameters on the velocity, temperature and nanoparticle volume fraction profiles are discussed through graphical illustrations. The impact of physical parameters on local skin friction coefficient, the rate of heat transfer and rate of mass transfer are shown in the tabulated form.